2014
DOI: 10.11648/j.ijnfs.20140306.26
|View full text |Cite
|
Sign up to set email alerts
|

A Review on: Antioxidant and Its Impact during the Bread Making Process

Abstract: Antioxidant compounds in food play an important role as a health protecting factor. Major sources of naturally occurring antioxidants are fruits, vegetables and whole grains. This review is focused on the classification, characteristics and mechanism of antioxidant and methodology were reported. Bread and bakery products have an important role in human nutrition. This review is focused also on Changes in antioxidant activity during the bread making process (mixing or dough, fermentation, and baking) and also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Cell wall degrading enzymes and fermentation by lactic acid bacteria and yeasts can influence the nutritional properties of bread by changing the levels and/or bioavailability of phenol compounds (Anson et al 2009(Anson et al , 2011Dordevic et al 2010;Hemery et al 2010;Ali Karrar 2014;Brewer et al 2014), sterols and vitamins (Katina et al 2007), enhancing the mineral bioavailability (Poutanen et al 2009), increasing the amount of soluble dietary fibers and bioactive peptides (Coda et al 2014), and reducing the starch digestibility and the glycemic response (Anson et al 2011;Coda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cell wall degrading enzymes and fermentation by lactic acid bacteria and yeasts can influence the nutritional properties of bread by changing the levels and/or bioavailability of phenol compounds (Anson et al 2009(Anson et al , 2011Dordevic et al 2010;Hemery et al 2010;Ali Karrar 2014;Brewer et al 2014), sterols and vitamins (Katina et al 2007), enhancing the mineral bioavailability (Poutanen et al 2009), increasing the amount of soluble dietary fibers and bioactive peptides (Coda et al 2014), and reducing the starch digestibility and the glycemic response (Anson et al 2011;Coda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing time of storage in the presence of berry flour may be connected to the significant content of phenolics that we noticed, as many studies document the antimicrobial effect of the polyphenols and recommend the commercial use of polyphenol rich extracts in food processing [26][27][28][29]. Sea buckthorn berries contain a series of biologically active substances, such as polyphenols and other natural antioxidants, which inhibit the development of microorganisms and allow the stabilization of the food matrix [30].…”
Section: Of 13mentioning
confidence: 94%
“…There are many researches which show that baking process causes a decrease of antioxidant capacity baked goods [64,[66][67][68]. The addition of different flours with a rich antioxidant activity might be able to enhance the antioxidant capacity of the final baked goods or to minimize its thermal losses [64,68,69].…”
Section: Radical Scavenging Activity Of Samplesmentioning
confidence: 99%
“…According to the literature there are also studies that showed an increase in the radical scavenging capacity of wheat-based products compared to flour and dough as a result of the conjugated phenolic compounds release, especially in crust. Moreover, these works attribute this increase in antioxidant capacity to the Maillard reaction too [56,68].…”
Section: Radical Scavenging Activity Of Samplesmentioning
confidence: 99%